FAKTOR PENENTU PENGGUNAAN BAHASA PADA MASYARAKAT TUTUR MAKASSAR: Kajian Sosiolinguistik di Kabupaten Gowa - Munira Hasyim (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2008)
This research discusses the Language Use of Makassar speech Society: The Sociolinguistics Study at Kabupaten Gowa. The discussion focuses on factors that determine the language use of Makassar speech society. The data are collected from speeches by the Makassar speech society at Kecamatan Somba Opu and Kecamatan Bontomarannu at Kabupaten Gowa. They are conversation, collected by observer’s paradox technique using tape recorder and field notes. The data are classified according to the types, patterns and use of its determining factors. The results of the study show several findings which determine the use of the languages: (a) skill of using the languages: when the speaker thinks that the addressee cannot speak BI, then the former chooses to use BM or BMM. (b) Setting and situation: when the place of speech is in the office or school, BI tends to be used. If it is in a place which is not official, BM or BMM tend to be used. (c) Participants: if the speaker thinks that the addressee is a close friend or relatives, BM is used. If the addressee is felt to be distant or respected, BI or BMM is used. (d) Objectives of speech: if the objective is to maintain Makassar culture, to teach something, to bargain something, BM or BMM is used. If it is to keep a secret, to give an official speech, to criticize, to tell humorous stories, to emphasize, BI or BMM is used.